1976
DOI: 10.1002/jss.400050304
|View full text |Cite
|
Sign up to set email alerts
|

Changes in E. coli cell envelope structure caused by uncouplers of active transport and colicin E1

Abstract: It is of interest to inquire whether agents that uncouple or deenergize membranes cause concomitant structural changes. The agents considered here are the uncoupler carbonyl cyanide-p-trifluoromethoxyphenylhydrazone and the bacteriocidal protein colicin E1, agents for which there is some precedent for believing that they interact with membranes. In intact E. coli ML 308-225 cells the inhibition of [14C]-PROLINE ACtive transport by FCCP increases with uncoupler concentration from approximately 20% at 2 muM to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

1978
1978
1990
1990

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“…Low-speed centrifugation (7,700 x g, 10 min) was found to remove the increased fluorescence from the sample, indicating that it was cell bound. The probe was also found to have undergone a shift in the emission maximum, from 440 to 410 nm, indicative of the probe being in a lipid environment (9,17).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Low-speed centrifugation (7,700 x g, 10 min) was found to remove the increased fluorescence from the sample, indicating that it was cell bound. The probe was also found to have undergone a shift in the emission maximum, from 440 to 410 nm, indicative of the probe being in a lipid environment (9,17).…”
Section: Resultsmentioning
confidence: 99%
“…An interpretation consistent with the data is that the cells lose their capacity to maintain the proton motive force, possibly as a result of either a recAinduced process or the imbalance in membrane composition. Loss of the potential across the membrane is known to have profound effects on outer membrane permeability (9,25).…”
Section: Resultsmentioning
confidence: 99%
“…Upon addition of CCCP to EDTA-treated cells preloaded with TMG, the cells rapidly lose all of their accumulated TMG (Fig. 4) (28), might simply allow CCCP to act as a sulfhydryl reagent on the TMG carrier protein (29,30). Yet Two recently received manuscripts bear on our findings and conclusions.…”
Section: Resultsmentioning
confidence: 99%
“…This change is sensitive to the state of membrane energization of the cell. Thus, energization decreases fluorescence intensity and deenergization reverses this effect [2][3][4][5]. Recently, we have shown that the alteration in fluorescence intensity in Escherichia coli has two components [6].…”
Section: Introductionmentioning
confidence: 99%